The Real Exchange Rate and Economic Growth - Eichengreen, Barry (World Bank, Washington, DC, 2017)
The real exchange rate was not at the center of the first generation of neoclassical growth models, nor was it prominent among the policy prescriptions that flowed from those models. Recent analyses, in contrast, have paid it more attention. This paper analyzes the role of the real exchange rate in the growth process, the channels through which the real exchange rate influences other variables, and policies useful (and not useful) for governing the real rate. An appendix provides econometric evidence supportive of the emphases in the text.